Community Preferences for Agrarian Reform in Kampung Reforma Agraria: A Case Study of Mekarsari Village, Banten - Gafuraningtyas, Dewi; Setiadi, Hafid; Koestoer, Raldi Hendro T (BHUMI: Jurnal Agraria dan Pertanahan, 2023)
Abstract: An agrarian reform program encompassing asset and access arrangement was implemented to address the inequality in land ownership. Furthermore, asset management and access management models are integrated in the same location to increase the effectiveness of the agrarian reform program. As a pilot project, the first Kampung Reforma Agraria (KRA) was implemented in Mekarsari Village, Panimbang District, Pandeglang Regency, by distributing land to 225 subjects. However, after five years of implementing agrarian reform, some subjects still have not occupied KRA locations. This condition indicates that some subjects are reluctant to live in the designated location. Therefore, this research aims to analyze the profile and characteristics of TORA subjects’ residences who have yet to occupy the land granted in the KRA and the influence of these two factors on their spatial preferences regarding agrarian reform policies. By interviewing 23 TORA subjects who had yet to occupy the Tanah Objek Reforma Agraria (TORA) location and transfer their land rights, the results show that 52.5% wanted to move to KRA. In contrast, 47.5% did not want to occupy their land in KRA. Based on the analysis of the physical characteristics of the TORA subjects’ residences, the relationship between the physical distance from the subject’s current residence to KRA and the subject’s preference to move to KRA was not very significant. The factors most influencing the subject’s preferences are the residence’s non-physical characteristics, the land’s current legal status, and the socio-economic profile. Based on these findings, policymakers responsible for setting the criteria for land recipients should enhance the supervision system for subject selection from the outset. Furthermore, when designing access provision programs, it is essential to account for the diverse preferences and needs of each subject group. Keywords: Agrarian Reform; Access Arrangement; Asset Arrangement; Kampung Reforma Agraria; Spatial Preferences.